Outage probability analysis of dual energy harvesting relay network over rayleigh fading channel using SC and MRC technique - Tan N. Nguyen; Minh Tran; Van-Duc Phan; Tran Thanh Trang (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, the system model of dual-energy harvesting relay network over Rayleigh fading channel and the comparison between Selecting Combining (SC) and Maximal Ratio Combining (MRC) technique cases are proposed and investigated. The closed-form expression of the outage probability for the SC case and the integral-form expression of the outage probability for MRC case is derived. Moreover, the influence of the main parameters on the system performance is demonstrated entirely by the Monte Carlo simulation. From the results, we can see that all simulation and analytical results match well with each other.